Functioning of the International Monetary System - Frenkel, Jacob (International Monetary Fund, 1996)
The fiftieth anniversary of the Bretton Woods Conference served as an opportunity to reappraise the desirability of strengthening the IMF's oversight of the functioning of the international monetary system. Whatever the design of an exchange rate system and the arrangements for the provision of international liquidity, it is widely accepted that to be effective such oversight must rest on a strong analytic foundation. These two volumes, edited by Jacob A. Frenkel and Morris Goldstein, present 30 analytic papers on the system as it functioned during 1987-91 and aim at conveying the flavor of those issues that commanded close attention in the Fund's research program.